2018
DOI: 10.1002/chem.201803246
|View full text |Cite
|
Sign up to set email alerts
|

C3−C3′ and C6−C6′ Oxidative Couplings of Carbazoles

Abstract: 9-Substituted carbazoles are widely used units in materials science, and their oxidative reactions have been utilized for the synthesis and characterization of polymers. Though the oxidative mechanism of carbazoles has been known for a few decades, structural definition has remained difficult, because their polymers are generally insoluble with incomplete characterization and unknown dependence of the electrochemical potentials. The oxidative reactions of 9-substituted carbazoles should be carefully considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 158 publications
1
11
0
Order By: Relevance
“…5-6), on M II PX self-assembled ITO (indium tin oxide) coated glass, coupling reactions of carbazolyls and vinyls in 0.5 mM M II XY after optimizing experimental condition were conducted by cyclic voltammetry (CV) at oxidative potential range (E = −0.50-1.0 V, 50 mV s −1 , 1 cycle, 1 min) and reductive potential range (E = −0.50 to −1.8 V, 50 mV s −1 , 1 cycle, 52 s), respectively. Both reactions were well studied by Bard's 21 , our 22 and worldwide groups [23][24][25] . The real-time optical and electrochemical monitoring can be used to ensure completely coupling proceed of each addition of monomer.…”
Section: Iterative Electrosynthesis Of Homo-organometallic Polymersmentioning
confidence: 99%
“…5-6), on M II PX self-assembled ITO (indium tin oxide) coated glass, coupling reactions of carbazolyls and vinyls in 0.5 mM M II XY after optimizing experimental condition were conducted by cyclic voltammetry (CV) at oxidative potential range (E = −0.50-1.0 V, 50 mV s −1 , 1 cycle, 1 min) and reductive potential range (E = −0.50 to −1.8 V, 50 mV s −1 , 1 cycle, 52 s), respectively. Both reactions were well studied by Bard's 21 , our 22 and worldwide groups [23][24][25] . The real-time optical and electrochemical monitoring can be used to ensure completely coupling proceed of each addition of monomer.…”
Section: Iterative Electrosynthesis Of Homo-organometallic Polymersmentioning
confidence: 99%
“…3 N -Functionalized carbazoles are particularly important as biologically active compounds and pharmaceuticals, 4 and are of prime interest in the fields of organic materials and polymers (Figure 1). 5 A broad array of synthetic methods exist to either de novo synthesize functionalized carbazole scaffolds, 6 or to selectively introduce new functional groups onto an appropriately prefunctionalized carbazole ring. The direct functionalizations of C–H or N–H bonds of the parent heterocycle via cross-dehydrogenative coupling, C–H activation, or the direct insertion of highly reactive carbenes or radicals are examples that allow the most atom-economic strategy to decorate the carbazole framework and is thus of major interest in organic synthesis.…”
mentioning
confidence: 99%
“…Figure S7, Supporting Information, shows the multicycled CV curves of BCz‐BO‐Azo ED process, a couple of newly generated peaks at 1.12 and 0.72 V corresponding to dimeric carbazole redox peaks and reduction peak were observed. [ 44 ] The peak current continuously increasing in every cycle indicated that the resistance of the ITO work electrode continued to increase, which meant that the resultant cross‐linked polymer by ED method of carbazole units generated and deposited on the surface of ITO work electrode as the growth of the CV scans. As shown in Figure S8, Supporting Information, the disappearance of peaks at 723 cm –1 and 750 cm –1 and the generation of peak in 734 cm –1 in the FTIR spectra indicate the disappearance of carbazole moiety and instead of dimeric carbazoles moiety, which revealed the relatively high polymerization degree of the ED film.…”
Section: Methodsmentioning
confidence: 99%